(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
The institutional European Union is facing two types of crisis. On the one hand, it needs to manage the current refugee’s influx efficiently and on the other hand it needs to deal with the democratic deficit that emerged by Europe’s incapacity to make the required decisions and gain the justification of its actions from its own people. This article aims firstly to highlight the legal framework (rule of law) that governs the asylum and migration procedures as well as the democratic gap that these provisions created in the different member states, as a crystal clear example of how a national competence became supranational. Furthermore, it illustrates the refugee profile, as a human being with acquired human rights through the theories of H. Arendt and the U. Beck. Lastly, the cosmopolitan approach is suggested in order to overcome the refugee crisis but a well-established integration should be the long term goal of Europe.